2017
DOI: 10.1097/ccm.0000000000002285
|View full text |Cite
|
Sign up to set email alerts
|

Antipyretic Therapy in Critically Ill Septic Patients: A Systematic Review and Meta-Analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…27,28 Retrospective and observational studies have even suggested benefit to elevated temperatures which in turn enhance the immune system and inhibit pathogen infectivity. [29][30][31][32][33][34][35] Our practice pattern was to utilize external or systemic temperature management devices to combat severe hyperthermia with the goal of inducing normothermia, not hypothermia. This practice pattern was left to the discretion of the attending intensivist as temperature management devices were limited and continually triaged among patients with the most severe hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Retrospective and observational studies have even suggested benefit to elevated temperatures which in turn enhance the immune system and inhibit pathogen infectivity. [29][30][31][32][33][34][35] Our practice pattern was to utilize external or systemic temperature management devices to combat severe hyperthermia with the goal of inducing normothermia, not hypothermia. This practice pattern was left to the discretion of the attending intensivist as temperature management devices were limited and continually triaged among patients with the most severe hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the panel had to consider indirect data extrapolated from studies in adults. One systematic review of adult patients studied the use of antipyretics and physical cooling methods included eight RCTs (1507 patients) and eight observational studies (17,432 patients) [361]. This study had 28-day mortality as the primary outcome, with additional outcomes of early mortality (i.e., death on or prior to day 14), frequency of acquisition of hospital-acquired infection, frequency of shock reversal, and mean changes in body temperature, heart rate, and minute ventilation.…”
Section: We Suggest Either Antipyretic Therapy or A Permissive Approamentioning
confidence: 99%
“…If the temperature increases without a greater proportional rise in heat production, overall entropy production is reduced; thus, suppressing fever where entropy production is decreased may be beneficial. Currently, antipyresis used indiscriminately in critically ill patients with sepsis has a minimal effect [ 92 ]. Analogously, therapeutic hypothermia, which involves cooling patients, may be useful in helping to maintain or enhance entropy production locally or systemically, provided the cooling does not reduce metabolism and heat production more than the drop in temperature.…”
Section: Evaluation and Implicationsmentioning
confidence: 99%